1991
DOI: 10.1002/mds.870060206
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic cervical dystonia: Clinical characteristics

Abstract: We reviewed detailed clinical features of 266 patients with idiopathic cervical dystonia, commonly called spasmodic torticollis. Mean age at onset (41 years), female-to-male ratio (1.9:1), clustering of onset between ages 30 and 59 (70%), familial history of dystonia (12%), and remissions (9.8%) were similar to those found in previous studies. In contrast to the single prior large clinical study of this disorder, no predominance of right-handers or significant thyroid disease was found. Pain, which occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
261
3
14

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(308 citation statements)
references
References 20 publications
30
261
3
14
Order By: Relevance
“…Another large series 2 reviewed 272 patients with CD and complete information about tremor and found that 71% had tremor; 60% had associated headneck tremor, and 27% had hand tremor phenomenologically identical to essential tremor. A larger series 6 showed a prevalence of head and hand tremor, respectively, of 50% and 32% in their 231 patients with CD, different from other report with similar sample that observed in 266 CD patients 28% had head tremor and 23% hand tremor 7 . our data are similar with the aforementioned studies; we found in 118 patients with CD, that 45 (38.2%) had head tremor and 24.5% of them also had postural hand tremor.…”
Section: Methodscontrasting
confidence: 53%
“…Another large series 2 reviewed 272 patients with CD and complete information about tremor and found that 71% had tremor; 60% had associated headneck tremor, and 27% had hand tremor phenomenologically identical to essential tremor. A larger series 6 showed a prevalence of head and hand tremor, respectively, of 50% and 32% in their 231 patients with CD, different from other report with similar sample that observed in 266 CD patients 28% had head tremor and 23% hand tremor 7 . our data are similar with the aforementioned studies; we found in 118 patients with CD, that 45 (38.2%) had head tremor and 24.5% of them also had postural hand tremor.…”
Section: Methodscontrasting
confidence: 53%
“…The high prevalence of pain (around 70% of patients) distinguishes cervical dystonia from other focal dystonias and contributes significantly to patient disability 19 . BoNT/A is highly effective in controlling pain, and its analgesic effect is sustained for a long time 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of patients spreaded to cranial segment, but we found a high prevalence of generalized spreading (28% of patients). Unfortunately, we did not test them for DYT1 mutation; it is known that patients with CD who are DYT1 mutation carriers are more prone to spread to generalized dystonia 1,13 .…”
Section: Discussionmentioning
confidence: 99%